THE STRATEGY OF COVERT RESISTANCE BY INDIGENOUS INTELLECTUALS IN RESPONSE TO COLONIAL EDUCATIONAL HEGEMONY IN INDONESIA - Muaz Tanjung; Muhammad Rifqi Irsyad (Journal of Contemporary Islam and Muslim Societies, 2026)
This history study analyses strategies of selective curriculum adaptation, subversive publications, and the formation of indigenous intellectual networks in response to colonial educational hegemony in Indonesia. The data are retrieved from historical sources on colonial education from the 19th to the early 20th centuries. The research finds that, in respond to the rigid ELS-HIS-Volksschool of the colonial system, indigenous intellectuals successfully exploited curricular loopholes and print media to revitalize local epistemology, alternative pedagogies, and journal publications. Furthermore, organizations such as Boedi Oetomo and Taman Siswa spread emancipatory visions, transforming education into a discursive contestation field. The effects of this contestation gradually eroded colonial dominance and laid the foundation for postcolonial national education. These findings have implications for the understanding of the historiography of colonial education and the development of postcolonial curriculum which remains relevant in the current dynamics of national education.